Prospective Evaluation of Posttraumatic Stress Disorder and Depression in Orthopaedic Injury Patients With and Without Concomitant Traumatic Brain Injury. Issue 9 (September 2017) - Roden-Foreman, Kenleigh; Solis, Jaicus; Jones, Alan; Bennett, Monica; Roden-Foreman, Jacob W.; Rainey, Evan E.; Foreman, Michael L.; Warren, Ann Marie
Abstract : Objectives: Psychological morbidities after injury [eg, posttraumatic stress disorder (PTSD) and depression] are increasingly recognized as a significant determinant of overall outcome. Traumatic brain injury (TBI) negatively impacts outcomes of patients with orthopaedic injury, but the association of concurrent TBI, orthopaedic injury, and symptoms of PTSD and depression has not been examined. This study's objective was to examine symptoms of PTSD and depression in patients with orthopaedic trauma with and without TBI. Design: Longitudinal prospective cohort study. Setting: Urban Level I Trauma Center in the Southwest United States. Patients/Participants: Orthopaedic trauma patients older than 18 years admitted for ≥24 hours. Main Outcome Measurements: Questionnaires examining demographics, injury-related variables, PTSD, and depression were administered during hospitalization and 3, 6, and 12 months later. Orthopaedic injury and TBI were determined based on ICD-9 codes. Generalized linear models determined whether PTSD and depression at follow-up were associated with TBI. Results: Of the total sample (N = 214), 44 (21%) sustained a TBI. Those with TBI had higher rates of PTSD symptoms, 12 months postinjury ( P = 0.04). The TBI group also had higher rates of depressive symptoms, 6 months postinjury ( P = 0.038). Conclusions: Having a TBI in addition to orthopaedic injury was associated with significantly higher rates of PTSD at 12 months and depression at 6 months postinjury. This suggests that sustaining a TBI in addition to orthopaedic injury places patients at a higher risk for negative psychological outcomes. The findings of this study may help clinicians to identify patients who are in need for psychological screening and could potentially benefit from intervention. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.